(untitled) (Tanzania Medical Journal, 2021)
ERRATUM: Saving Lives through Voluntary Blood Donation: Learning from Medical Students in Ruvuma, Southern Tanzania Moshi M. Shaaban, Kauke B. Zimbwe, Bernard Mbwele In the original version of this article, the name of author Moshi M. Shaaban was incorrectly written, the correct name is Moshi. M. Shabani. Reference Moshi M. Shabani, Kauke B. Zimbwe, Bernard Mbwele, Saving Lives through Voluntary Blood Donation: Learning from Medical Students in Ruvuma, Southern Tanzania, TMJ Vol 31 No. 4 (2020); 1-20.